Meningkatkan Kemampuan Menulis Bahasa Jepang Melalui Media Padlet - Rizki Maulina Handini (Diponegoro University, 2020)
This research is based on efforts to improve writing skills in Japanese. Writing activities are an important aspect of learning a language. This study used samples from beginner-level Japanese learners, namely apprentices at LPK JLMC Lembang, West Java. The research design used in this study is true experimental, using the experimental class and the control class in research activities as a comparison of whether or not the effectiveness of the padlet media in learning to write Japanese. The writing activity referred to in this research is writing danraku (paragraphs) in the form of short essays using padlet as a media for doing exercises. The first step in this study was to carry out a pre-test on the control class and the experimental class. Furthermore, the treatment with padlet media was carried out five times in the experimental class. The final step is to provide post-test to the experimental class and control class, as well as to distribute a special questionnaire for the experimental class. The results showed that the use of padlet media was quite effective in learning to write Japanese. This is based on the N-Gain test which shows the figure of 58%. Furthermore, based on the results of the questionnaire, it was found that an attractive padlet display could increase learner motivation in writing activities. In addition, the use of letters, vocabulary and sentence patterns can be improved.